DNA and Due Process - Garrett, Brandon L. (2010)
The U.S. Supreme Court in District Attorney's Office v. Osborne confronted novel and complex constitutional questions regarding the postconviction protections offered to potentially innocent convicts. Two decades after DNA testing exonerated the first inmate in the United States, the Court heard its first claim by a convict seeking DNA testing that could prove innocence. I argue that, contrary to early accounts, the Court did not reject a constitutional right to postconviction DNA testing. Despite language suggesting the Court would not constitutionalize the issue by announcing an unqualified freestanding right, Chief Justice Roberts's majority opinion proceeded to carefully fashion an important, but qualified and derivative procedural due process right. While denying relief to Osborne for narrow factual and procedural reasons, the Court's ruling swept more broadly. The Court held that states with postconviction discovery rules, as almost all have enacted, may not arbitrarily deny access to postconviction DNA testing, and then pointed to the generous provisions of the federal Innocence Protection Act as a model for an adequate statute. The Court also continued to assume that litigants may assert constitutional claims of actual innocence in habeas proceedings. In this Essay, I explore the contours of the Osborne due process right, its larger implications for constitutional interpretation, and, more specifically, whether the decision has the potential to create pressure on the States to provide meaningful avenues for convicts to litigate their innocence